SALES PROMOTION TECHNIQUES AND THEIR INFLUENCE ON CONSUMER AWARENESS OF ELECTRONIC BRANDS IN RIVERS STATE - Braide, Tamunotonye Grace (International Research Journal of Arts and Communication, 2025)
This study investigates Sales promotion techniques and brand recognition of electronic stores in Rivers State. The study adopted survey research design. Based on the research questions, hypotheses were formulated. Using convenience sampling procedure, thirty-six (36) electronics stores were simple randomly selected and 3 copies of questionnaire were given to each firm making it one hundred and eight (108) copies distributed to only management staff. The questionnaire was structured using a five-point likert scale, Spearman Rank Order Correlation was used to test if the independent variable and its dimensions as associated with the dependent variable. The findings revealed that Sales promotion techniques have a strong positive association with brand recognition of electronic stores in Port Harcourt. We therefore recommend that electronic firms/dealers should maintain the policy of aligning their Sales promotion techniques to reflect quick recognition of their brand